Pengaruh Inventory Intensity, Kepemilikan Institusional dan Komisaris Independen Terhadap Tax Avoidance (Studi Empiris Pada Perusahaan Sektor Pertambangan Batu Bara yang terdaftar di Bursa Efek Indonesia Tahun 2018 - 2022) - Febriyani, Yesi; Oktapiani, Eka (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2023)
This study aims to determine the effect of Inventory Intensity, Institutional Ownership and Independent Commissioners on Tax Avoidance in coal mining companies listed on the Indonesia Stock Exchange. The research period used is the 2018-2022 period. The type of research used in this research is quantitative with secondary data methods. Determination of the research sample using purposive sampling method and based on existing criteria obtained 35 company data and analyzed using panel data regression technique with random effect model to test the hypothesis. Testing the hypothesis in this study uses multiple linear regression using Eviews version 10. The results of this study indicate that simultaneously it shows that Inventory Intensity, Institutional Ownership and Independent Commissioner jointly affect tax avoidance. The ability of the independent variable to explain the dependent variable is 12% while the remaining 88% is explained by other variables outside this research model. The results of this study show that partially, inventory intensity and institutional ownership have no effect on tax avoidance. Meanwhile, the independent commissioners partially influence tax avoidance.